IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM PEMBELAJARAN AKUNTANSI - Susilowati, Nurdian; Safitri, Desti Galuh (Universitas Muhammadiyah Surakarta, 2024)
This study aims to investigation of internalization profil pelajar pancasila in shaping accounting knowledge and ethics. Quantitative research strategy has been adopted. This research design uses a pre-experimental research design. The design used is One Group Pretest-Posttest Design. The respondents were 34 accounting students who attended Profil Pelajar Pancasila. The result shows that there is increase in accounting ethics and students accounting understanding after the Pancasila student profile strengthening project. This Pancasila student profile strengthening project was implemented with project-based learning. This project-based learning was carried out with students having to prepare financial reports of costs from entrepreneurial activities. Project-based learning with entrepreneurial activities was able to improve students' accounting understanding in preparing financial reports of costs. In addition, in the process of preparing financial reports of costs, students accounting ethics also increased.